The Relationship Between Business Competition Law and Commercial Law in Ensuring Healthy Business Competition in the Market - Muhammad Irfan Syah; Yuni Dhea Utari; Koni Piranda; Muhammad Rizky Anes (Penerbit Hellow Pustaka, 2024)
This research aims to discuss the relationship between business competition law and trade law in realizing healthy business competition in Indonesia. The method used is literature study through document review, such as journals, books and related literature. The results of the discussion show that business competition law, which is regulated in Law no. 5 of 1999, aims to prevent monopoly and unfair competition practices. The basic principles include freedom of business, healthy competition, efficiency and openness. Meanwhile, commercial law regulates legal relations in trade, providing order and legal certainty for business actors. These two areas of law complement each other in creating a healthy and just economic system. Business competition law plays a role in preventing unhealthy business practices and promoting efficiency, while trade law regulates commercial transactions and legal relations between business actors. Both contribute to protecting consumers, increasing economic efficiency, and promoting sustainable economic growth. It can be concluded that business competition law and trade law have an important and complementary role in creating a healthy and conducive business climate for economic growth in Indonesia. Harmonization and effective law enforcement in these two fields is the key to realizing healthy and fair business competition.